Getting started with oVirt 3.3 : a practical guide to successfully implementing and calibrating oVirt 3.3, a feature-rich open source server virtualization platform /: a practical guide to successfully implementing and calibrating oVirt 3.3, a feature-rich open source server virtualization platform. (2013) - Unknown
No abstract available